Nonlinear distortion of nonreciprocal transmission in parity-time-symmetric silicon micromechanical resonators - Rui Wang; Lei Han; Man-Na Zhang; Li-Feng Wang; Qing-An Huang (Microsystems & Nanoengineering)
Abstract Parity-time (PT) symmetric resonators have an exact phase with real frequency eigenvalues and a broken phase with complex-conjugate frequency eigenvalues. In the presence of nonlinear gain, the PT-symmetric resonator exhibits nonreciprocal transmission when it is biased at the broken phase, which promises applications for isolators and circulators in modern communication systems. The nonlinear distortion performance is one of the most important metrics in most electronic applications where linearity is critical. This article provides the first experimental results of nonlinear distortion of nonreciprocal transmission in a pair of electrically coupled silicon micromechanical resonators at the broken phase. The results show the 1 dB gain compression point (P1dB) with 5 dBm and the input-referred third-order intercept point (IIP3) with 11.5 dBm.